GOTHIC 8.1 Benchmark to ThAI Facility Experiment with Steam-Helium Stratification. (1st November 2016) - Moore, T. M.; George, T. L.
Abstract: The Thermal hydraulics, Aerosols and Iodine (ThAI) facility, located in Eschborn, Germany, is a 60-m 3 steel test vessel designed to simulate operational and accident conditions in a nuclear containment structure. The ThAI facility provides experimental data used for validation of thermal-hydraulic codes. The test performed at this facility has been modeled using the GOTHIC 8.1(QA) software package for the purpose of validating both physical models and modeling techniques. The test analyzed is from step 2 of the International Standard Problem 47 test performed at the ThAI facility. This test consisted of three injection ports for steam and helium to enter the vessel off-axis. The off-axis injection locations along with the compartmented geometry of the facility provide a complex coupling of physics that would be present in an accident transient inside the containment of a typical light water reactor. Key considerations of this analysis are stratification of the steam and helium, condensation deposition, and flow patterns within the vessel.